KEEFEKTIFAN MODEL PEMBELAJARAN RQA (READING QUESTION AND ANSWERING) BERBANTU LKPD UNTUK MENINGKATKAN KEMANDIRIAN DAN HASIL BELAJAR MATEMATIKA SISWA KELAS 4 SEKOLAH DASAR - Erna Pujiyanti; Sumarno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
ABSTRACT The formulation of the problem in this research is how effective the study from home RQA (reading question and answering) learning model is in increasing the independence and learning outcomes of 4th grade elementary school students in Tembalang District, Semarang Regency. he approach used in this research is a quantitative approach. Using the pretest-pottest control group design. Data collection techniques using tests, and observations, normality tests, homogeneity tests, independent sampel t test and gain index calculations. he results of the study showed that the reading question and answering (RQA) learning model was effective in increasing the independence and mathematics learning outcomes of fourth grade elementary school students. This is evidenced by the results of the independent sample t test on student learning independence by obtaining a Tcount of 3.635 > Ttable 1.99962 and a significance level of 0.001 <0.05. Then test independent sample t test on student learning outcomes by obtaining a Tcount of 5.221 > T table 1.99962 and a significance level of 0.001 <0.05. These results indicate that the Reading Question and Answering (RQA) learning model is more effective in increasing the independence and learning outcomes of fourth grade students of SD Negeri Tembalang District.